THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE KALIDERES VILLAGE OFFICE, WEST JAKARTA ADMINISTRATIVE CITY - Naufal Aiz Syafirhad; Suharini; Ratih Hastasari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Employee performance is a key factor in improving organizational effectiveness, particularly in public sector institutions. This study aims to examine the influence of leadership style and work motivation on employee performance at the Kalideres Subdistrict Office, West Jakarta Administrative City. A quantitative approach was employed using a saturated sampling technique, involving all 130 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The results indicate that leadership style and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. The Adjusted R Square value of 0.873 indicates that the two independent variables explain 87.3% of the variance in employee performance, while the remaining 12.7% is explained by other factors outside the research model. These findings suggest that strengthening leadership practices and enhancing employees' work motivation are essential strategies for improving performance in public sector organizations.